Assessment of Workplace Violence and Its Consequences among Emergency Department Nurses: A Cross-Sectional Study - Jasim, Mohammed Salih (Jurnal Berita Ilmu Keperawatan, 2025)
Workplace violence against nurses in Emergency Departments (ED) is a universal problem that impacts the well-being of staff and quality of care, specifically in Mosul City, Iraq, where healthcare workers continuously report aggression. The present study assesses experiences of workplace violence against ED nurses in Mosul, its characteristics and types, along with effective interventions by targeting factors contributing to the underlying reasons. A quantitative, cross-sectional study with 111 nurses from four large public hospitals in Ninevah, Mosul. Demographic data, experience of violence, causes, and perceptions concerning the attitude of nurses relating to reporting and retaliation were determined from the demographic questionnaire and a structured questionnaire based on the Workplace Violence in Healthcare Scale (WVHS), which had been previously validated. Primary data analysis used descriptive and inferential statistics. Verbal abuse and physical assault (78%) were the most common types of violence, followed by sexual harassment, bullying, and racial/ethnic harassment. Emergency department overcrowding was associated with an increased likelihood of staff reporting being cut, stabbed, or shot, with at least one contributing factor in all eight categories. More than half of nurses (53.2%) reported experiencing moderate workplace violence, which caused difficulties with physical health, caregiver functioning, and relationships. Workplace violence in Mosul Emergency Departments is a widespread and multi-faceted issue that will require whole-system approaches, such as improved staffing, targeted training, and legal protection, to improve the safety of work areas